2023
DOI: 10.1186/s11658-023-00482-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-15b-5p and PCSK9 inhibition reduces lipopolysaccharide-induced endothelial dysfunction by targeting SIRT4

Abstract: Background Endothelial dysfunction and deregulated microRNAs (miRNAs) participate in the development of sepsis and are associated with septic organ failure and death. Here, we explored the role of miR-15b-5p on inflammatory pathways in lipopolysaccharide (LPS)-treated human endothelial cells, HUVEC and TeloHAEC. Methods The miR-15b-5p levels were evaluated in LPS-stimulated HUVEC and TeloHAEC cells by quantitative real-time PCR (qRT–PCR). Functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Inhibitors of these molecules can reverse the LPS-induced downregulation of SIRT4 expression, attenuate the inflammatory cascade triggered in endothelial cells by LPS, and mitigate their damage and death. This suggests that the functional effects of miR-15b-5p and PCSK9 can, at least in part, be attributed to their ability to modulate SIRT4 expression ( 72 ). Earlier research also found that SIRT4 could mitigate the LPS-induced expression of pro-inflammatory cytokines and adhesion molecules in HUVECs by blocking the nuclear translocation of NF-κB p65 ( 73 ).…”
Section: Sirts and Pathophysiology Of Sepsismentioning
confidence: 99%
“…Inhibitors of these molecules can reverse the LPS-induced downregulation of SIRT4 expression, attenuate the inflammatory cascade triggered in endothelial cells by LPS, and mitigate their damage and death. This suggests that the functional effects of miR-15b-5p and PCSK9 can, at least in part, be attributed to their ability to modulate SIRT4 expression ( 72 ). Earlier research also found that SIRT4 could mitigate the LPS-induced expression of pro-inflammatory cytokines and adhesion molecules in HUVECs by blocking the nuclear translocation of NF-κB p65 ( 73 ).…”
Section: Sirts and Pathophysiology Of Sepsismentioning
confidence: 99%
“…According to published methods, 10 mmol/L β-gp, 20ug/m dexamethasone and 50ug/ mL L-ascorbic acid were added to the routine medium to induce osteogenesis of VSMCs for 7 days, the medium were changed every 2/3 days (24-29). To mimic the effects of PCSK9i in vivo, 100 μg/mL of reagent-grade purified evolocumab (Selleck, America) was used to co-incubate with VSMCs for 7 days during osteogenesis induction (30)(31)(32). To mimic the stimulation of VSMCs by PCSK9 protein in vivo, refer to previous research (33), 0 μg/mL, 0.55 μg/mL, 1.1 μg/mL, 2.2 μg/mL, and 4.4 μg/mL of recombinant human PCSK9 (MedChemExpress, USA) were co-incubated with VSMCs for 7 days, and the concentration exhibiting the highest intracellular calcium content was chosen for subsequent experimental procedures.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Conversely, inhibition of the autophagy pathway may likewise ameliorate sepsis-induced organic depression. In the pathogenesis of sepsis, for instance, it has become clear that suppressing autophagy mechanisms by targeting SIRT4, MAPKs, and Nrf2 pathways may be a useful strategy for protecting organ function [177][178][179]. Indeed, it has also been demonstrated that autophagy is activated early in the onset of sepsis, but that as the condition progresses, autophagic activity declines [180,181].…”
Section: The Regulatory Role Of M 6 a Methylation Modified Autophagy ...mentioning
confidence: 99%